Eggs in one basket: Security and convenience of digital currencies - Charles M. Kahn; Francisco Rivadeneyra; Tsz-Nga Wong (Bank of Canada, 2021)
Digital currencies store balances in anonymous electronic addresses. We analyze the tradeoffs between the safety and convenience of aggregating balances in addresses, electronic wallets and banks. In our model, agents balance the risk of theft of a large account with the cost to safeguarding a large number of passwords for many small accounts. Account custodians (banks, wallets and other payment service providers) have different objectives and trade-offs along these dimensions; we analyze the welfare effects of differing industry structures and interdependencies. In particular, we examine, the consequences of "password aggregation" programs, which, in effect, consolidate risks across accounts.
Keywords: E; E4; E42; E5; E51; E58; 330; Digital currencies and fintech; Financial services; Payment clearing and settlement systems; Central bank research